The potential usefulness of virtual reality systems for athletes: A short SWOT analysis - Düking, P.; Holmberg, H. C.; Sperlich, B. (Frontiers in Physiology, 2018)
Virtual reality (VR) systems (Neumann et al., 2017), which are currently receiving considerable attention from athletes, create a two- or three-dimensional environment in the form of emulated pictures and/or video-recordings where in addition to being mentally present, the athlete even often feels like he/she is there physically as well. As she/he interacts with and/or reacts to this environment, movement is captured by sensors, allowing the system to provide feedback.